Comparison of Simulation-Based versus Cadaveric-Tissue-Based Ocular Trauma Training on Novice Ophthalmologists: Repair of Corneal Laceration Model - Purt, Boonkit; Ducey, Timothy; Sykes, Sean; Pasternak, Joseph F.; Ryan, Denise S.; Sia, Rose K.; Colyer, Marcus H. (Journal of Academic Ophthalmology, 2021)
Purpose The aim of this study was to evaluate whether the simulated tissue models may be used in place of animal-based model for corneal laceration repair for surgical skills acquisition.Design Prospective randomized controlled trial.Participants Seventy-nine military and civilian 2nd- and 3rd-year ophthalmology residents and 16 staff ophthalmologists participating in the Tri-Service Ocular Trauma Skills Laboratory at the Uniformed Services University (Bethesda, MD).Methods Resident ophthalmologists underwent preliminary evaluation of their ability to close a 5-mm linear, full-thickness corneal laceration involving the visual axis. They then were randomized to undergo 90 to 120 minutes of either simulator-based (SIM) or swine cadaveric-tissue-based (CADAVER) corneal laceration repair. The same evaluation was performed post training. On a more limited basis, the study was repeated for attending ophthalmologists to act as a pilot for future analysis and test efficacy for “refresher” training.Main Outcome Measures Successful wound closure with secondary outcomes of suture length, tension, depth, and orientation, as graded by attending ophthalmologists.Results No significant difference in CADAVER versus SIM groups in the primary outcome of watertight wound closure of the corneal laceration. CADAVER group performed better than SIM group for certain metrics (suture depth, p = 0.009; length, p = 0.003; and tension, p = 0.043) that are associated with poor wound closure and increased amount of induced corneal astigmatism. For attending ophthalmologists, six of the eight in each group (SIM and CADAVER) retained or improved their skills.Conclusions For resident ophthalmologists, SIM training is sufficient for achieving the primary outcome of watertight wound closure. However, CADAVER training is superior for wound metrics for the ideal closure. For attending ophthalmologists, SIM training may be useful for retention of skills.
Keywords: ophthalmology; simulation; training; cornea; trauma